Relationship between anterior disc displacement with/without reduction and effusion in temporomandibular disorder patients using magnetic resonance imaging - Koh, Kwang-Joon (Korean Academy of Oral and Maxillofacial Radiology, 2013)
PURPOSE: This study was performed to evaluate the relationship between anterior disc displacement and effusion in temporomandibular disorder (TMD) patients using magnetic resonance imaging (MRI). MATERIALS AND METHODS: The study subjects included 253 TMD patients. MRI examinations were performed using a 1.5 T MRI scanner. T1- and T2-weighted images with para-sagittal and para-coronal images were obtained. According to the MRI findings, temporomandibular joint (TMJ) disc positions were divided into 3 subgroups: normal, anterior disc displacement with reduction (DWR), and anterior disc displacement without reduction (DWOR). The cases of effusion were divided into 4 groups: normal, mild (E1), moderate (E2), and marked effusion (E3). Statistical analysis was made by the Fisher's exact test using SPSS (version 12.0, SPSS Inc., Chicago, IL, USA). RESULTS: The subjects consisted of 62 males and 191 females with a mean age of 28.5 years. Of the 253 patients, T1- and T2-weighted images revealed 34 (13.4%) normal, DWR in 103 (40.7%), and DWOR in 116 (45.9%) on the right side and 37 (14.6%) normal, DWR in 94 (37.2%), and DWOR in 122 (48.2%) joints on the left side. Also, T2-images revealed 82 (32.4%) normal, 78 (30.8%) E1, 51 (20.2%) E2, and 42 (16.6%) E3 joints on the right side and 79 (31.2%) normal, 85 (33.6%) E1, 57 (22.5%) E2, and 32 (12.7%) E3 on the left side. There was no difference between the right and left side. CONCLUSION: Anterior disc displacement was not related to the MRI findings of effusion in TMD patients (P>0.05).